ANALISIS PENERAPAN ALOKASI DANA DESA (ADD) DALAM UPAYA MENINGKATKAN PEMBANGUNAN DESA (Studi Kasus Pada Desa Suwaan, Kecamatan Kalawat, Kabupaten Minahasa Utara) - Ruru, Novianti; Kalangi, Lintje; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The ADD (Alokasi Dana Desa) program is one of the part from APBD (Anggaran Pendapatan dan Belanja Daerah) that allocated to fulfill the needs, role of the government, and to support the village development. ADD program is one of the sources of income that can be related to support the village development in order to improve the welfare of the villagers. This study aims to find out the implementation of the ADD program in efforts to increase the rural growth. This study is qualitative research. The result shows that the village government has been properly applying the standard of the ADD program based on North Minahasa regulation No. 22, 2016. Keywords : ADD program, implementation of ADD, rural development